2018
DOI: 10.1002/jor.23871
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical influence of deficient posterolateral corner structures on knee joint kinematics: A computational study

Abstract: The posterolateral corner (PLC) structures including the popliteofibular ligament (PFL), popliteus tendon (PT) and lateral collateral ligament (LCL) are important soft tissues for posterior translational, external rotational, and varus angulation knee joint instabilities. The purpose of this study was to determine the effects of deficient PLC structures on the kinematics of the knee joint under gait and squat loading conditions. We developed subject-specific computational models with full 12-degree-of-freedom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…Thus, it was proved that PCL injury significantly influences posterior stability during high flexion in UKA. 44 Our results showed that an increased posterior tibial slope maintained posterior stability in PCL-deficient UKA. This implies that decreased posterior tibial slope maintains anterior stability in the ACL-deficient UKA.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Thus, it was proved that PCL injury significantly influences posterior stability during high flexion in UKA. 44 Our results showed that an increased posterior tibial slope maintained posterior stability in PCL-deficient UKA. This implies that decreased posterior tibial slope maintains anterior stability in the ACL-deficient UKA.…”
Section: Discussionsupporting
confidence: 58%
“…Furthermore, the contact stress on the articular cartilage and the kinematics are consistent with the results reported in previous studies. 44 , 45 In addition, this study has two strengths compared to other studies. First, in contrast to those of previous UKA studies, the tibia, femur, and related soft tissues were included in the FE model.…”
Section: Discussionmentioning
confidence: 98%
“…The patient-specific lateral UKA insert was designed using a previously existing 3D knee joint model. 20 - 22 CT and MRI scans were initially performed. The image data were imported into Mimics version 14.1 (Materialise, Leuven, Belgium) for 3D reconstruction.…”
Section: Methodsmentioning
confidence: 99%
“…The previously mentioned 3D medical imaging data used for a patient-specific lateral mobile UKA development were used in the development of the finite element (FE) model ( Figure 2 ). 20 - 23 3D bone and soft tissue models were reconstructed from CT and MRI, as described in previous studies. 18 , 23 , 24 All the ligament bundles were modelled as non-linear springs, and the material properties were obtained from previous studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation